ANALISIS PENGUKURAN KINERJA PADA DINAS PERHUBUNGAN KAB. MANDAILING NATAL BERBASIS BALANCED SCORECARD (BSC) - Heriyanti Tampubolon; Sri Muljaningsih; Setyo Tri Wahyudi (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
The performance of local governments are much under the spotlight. People are asking the benefits of public services. Now the Department of Transportation Mandailing Natal using LAKIP as performance reports. But the performance is reflected in LAKIP often it is not the actual condition. SAKIP still limited to the determination of the vision, mission and goals of the organization. The purpose of this research are: (1) to formulate the design performance measurement system based on the BSC approachment at the Department of Transportation Mandailing Natal, (2) to formulate the design of strategic maps that the relevant for the Department of Transportation Mandailing Natal and  (3) analyze the results of performance measurement at the Department of Transportation Mandailing Natal based on the BSC in 2018. The method used are the AHP and BSC with four perspectives: financial perspective, customer perspective, perspective of business process internal and learning and growth perspective. The results design of the performance measurement system consists of 10 strategic goals and 17 Key Performance Indicators (KPI). The result of AHP is the customer's perspective (0.557), the financial perspective (0.273), internal business process perspective (0.087) and learning and growth perspective (0.083). And the results of performance measurement Mandailing Natal Department of Transportation in 2018 is 71.97% (red = less). Score the highest performance is the perspective of learning and growth of 85.48% (yellow), score the performance of internal business process perspective is 75.72% (red) score financial perspective is 70.24% (red) to score the performance of the customer's perspective score is 70.22% (red).